Cole Crops: Broccoli, Cabbage and Cauliflower - Marr, Charles W.; Tisserat, Ned (My University, 1998)
This publication is for commercial vegetable production specifically, cole crops in Kansas. This includes broccoli, cabbage, and cauliflower.
MF1108_1998_11
Keywords: MF1108; Crops; Fruits and Vegetables; Equipment and Structures; MF